Level of Knowledge and Attitudes of Nursing Students Prodi Pekalongan on Implementation Practice Nurses Registration Regulations - Zaenal Zaenal; Amirudin Ta’adi; Hartati Hartati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Permenkes 148/Menkes/Per/I/2010 Number of Permits and Enforcement Practice Nurse with all applicable provisions have been published. The reality show is still a lot of medical acts performed by nurses. The purpose of this study is to provide an overview of the level of knowledge and attitude of nursing students Prodi Pekalongan on the implementation of the rules and practices of nurse registration, rights, duties and authority of nurses. This research method is a quasi-experimental design with pre and post test. The student population was nursing Pekalongan Prodi, as many as 80 students and as many as the population of samples taken. Analysis of the data using the Sign-rank test (Wilcoxon test) with significance ρ 0.05. Wilcoxon statistics obtained from the difference of knowledge (ρ = 0.000), attitude (ρ = 0.000) after the implementation of Regulation Regitrasi socialization Practice Nurses, Rights, Duties, Powers Nurse.